2021
DOI: 10.1097/md.0000000000027414
|View full text |Cite
|
Sign up to set email alerts
|

Favorable colorectal cancer mortality-to-incidence ratios in countries with high expenditures on health and development index

Abstract: Background: Global variation in the incidence and outcomes of colorectal cancer (CRC) is associated with many factors, among which screening policies and early treatment play substantial roles. However, screening programs and intense treatment are expensive and require good health care systems. For CRC, no clear association has yet been established between clinical outcomes and health care disparities.Method: We used the mortality-to-incidence ratio (MIR) of CRC as a measure of clinical outcomes for comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Colorectal cancer (CRC) is the third most frequent cancer in the world and the second leading cause of death related to cancer. The highest rates of morbidity are in Australia and Europe (more than 40/100,000 among men), and the highest mortality rate is in Eastern Europe (more than 20/100,000 among men) [ 3 , 4 ]. It is likely that this situation will intensify in the upcoming decades, particularly in wealthy countries [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is the third most frequent cancer in the world and the second leading cause of death related to cancer. The highest rates of morbidity are in Australia and Europe (more than 40/100,000 among men), and the highest mortality rate is in Eastern Europe (more than 20/100,000 among men) [ 3 , 4 ]. It is likely that this situation will intensify in the upcoming decades, particularly in wealthy countries [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…This finding is consistent with that of a study on BC epidemiology using MIR proxy from the Global Burden of Disease study data, which found that an inverse correlation was observed between the BC MIR and HDI values, with less developed countries having BC survival statistics ( 17 ). The concept of lower cancer MIR in more developed countries and regions has been examined for several malignancies like colorectal, gastric, prostate, oral cavity, kidney, and liver cancers, all of which indicated the impact of socioeconomic development on improving cancer outcomes from an epidemiological aspect ( 12 , 13 , 16 , 19 , 21 , 24 , 51 ). The findings of this study confirmed most of the studies that used MIR to study cancer care and evaluate healthcare disparities.…”
Section: Discussionmentioning
confidence: 99%
“…One of the well-known and validated proxies of the quality of care, especially for cancer causes, is the mortality-to-incidence ratio (MIR), which has been shown to be a beneficial indicator of global cancer screening and care ( 11 ). To date, MIR has been recruited on various aggregated databases to examine the cancer care status and disparities among different geographic and socioeconomic categories for several cancers, including colorectal ( 11 , 12 ), liver ( 13 ), pancreatic ( 14 ), gastric ( 15 , 16 ), breast ( 17 , 18 ), prostate ( 19 ), and kidney cancers ( 20 , 21 ), and the results have been encouraging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the expense of the current screening tests and treatment options, the prognosis of NPCs might be linked to economic status. However, compared with cancers with more established or feasible screening strategies and more therapeutic options, the correlations between MIR and healthcare expenditure on NPC are not as significant as correlations with lung cancer, colorectal cancer, gastric cancer, and lip and oral cancer [ 16 , 17 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%